2018
DOI: 10.1021/acs.nanolett.8b01003
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin Bismuth Film on 1T-TaS2: Structural Transition and Charge-Density-Wave Proximity Effect

Abstract: We have fabricated bismuth (Bi) ultrathin films on a charge-density-wave (CDW) compound 1T-TaS and elucidated electronic states by angle-resolved photoemission spectroscopy and first-principles band-structure calculations. We found that the Bi film on 1T-TaS undergoes a structural transition from (111) to (110) upon reducing the film thickness, accompanied by a drastic change in the energy band structure. We also revealed that while two-bilayer-thick Bi(110) film on Si(111) is characterized by a dispersive ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…Experimentally, Bi prefers the formation of α‐bismuthene film at a small thickness when deposited on Si(111), [110a] highly oriented pyrolytic graphite (HOPG), [110b,c] 1T−TaS 2 [37] and graphene/SiC substrates, [36] while β‐bismuthene is favored for thicker film. For example, upon reducing the thickness of Bi films from 8 layers to 2 layers on the 1T−TaS 2 , the 2D Bi films underwent a structural transition from buckled to puckered structure [37] . By using sonochemical exfoliation approach, Lu et al.…”
Section: Synthesis Of 2d Metallic Materialsmentioning
confidence: 99%
See 3 more Smart Citations
“…Experimentally, Bi prefers the formation of α‐bismuthene film at a small thickness when deposited on Si(111), [110a] highly oriented pyrolytic graphite (HOPG), [110b,c] 1T−TaS 2 [37] and graphene/SiC substrates, [36] while β‐bismuthene is favored for thicker film. For example, upon reducing the thickness of Bi films from 8 layers to 2 layers on the 1T−TaS 2 , the 2D Bi films underwent a structural transition from buckled to puckered structure [37] . By using sonochemical exfoliation approach, Lu et al.…”
Section: Synthesis Of 2d Metallic Materialsmentioning
confidence: 99%
“…[37][38][39]110] Figures 2c,d shows the top and side views of the αand β-bismuthene, which exhibit a puckered black-phosphorus-like structure and a buckled graphene-like structure corresponding to the Bi (110) and Bi (111) plane, respectively. Ab initio molecular dynamics simulations indicated that both geometries have good thermal stability and could keep stable up to 700 K. [111] Experimentally, Bi prefers the formation of α-bismuthene film at a small thickness when deposited on Si(111), [110a] highly oriented pyrolytic graphite (HOPG), [110b,c] 1TÀ TaS 2 [37] and graphene/SiC substrates, [36] while β-bismuthene is favored for thicker film. For example, upon reducing the thickness of Bi films from 8 layers to 2 layers on the 1TÀ TaS 2 , the 2D Bi films underwent a structural transition from buckled to puckered structure.…”
Section: Bimentioning
confidence: 99%
See 2 more Smart Citations
“…The Bi(111) shows rhombohedral crystalline structure of the bulk Bi. Other substrates such as Bi 2 Te 3 , 1T‐TaS 2 , and highly oriented pyrolytic graphite (HOPG) have also been used for the preparation of α ‐ bismuthene . It is relatively more stable on HOPG due to electron transfer from the HOPG to the Bi films …”
Section: Synthesis Structure and Propertymentioning
confidence: 99%